The Mediating Role of Person-environment Fit in The Relationship between Perceived Servant Leadership and Flourishing at Work - Taha, Heba (The Arab Journal of Administration, 2021)
This study aimed to examine the relationship between perceived servant leadership (leader follower -focus, leader purposefulness and leader goal- orientation) and flourishing at work (emotional well-being, psychological well-being and social well-being) and the mediating role of person-environment fit in this relationship. The study adopted a descriptive analytical approach and a questionnaire as a main tool for data collection. It was conducted on a stratified random sample of (284) teaching assistants from all faculties of Assiut University. By using Simple and Stepwise Multiple Regression in analyzing results, the findings showed that leader purposefulness which is one dimension of perceived servant leadership was significantly and positively correlated with both of person- environment fit and all dimensions of flourishing at work. The results showed also that there was a significant positive correlation between person- environment fit and all dimensions of flourishing at work. Furthermore, the results showed that person- environment fit completely mediated the relationship between perceived servant leadership and flourishing at work particularly social well-being. Finally, the results of Stepwise Multiple Regression proved the removal of leader follower- focus in all relations between the variables of the study. The findings of this study highlighted some recommendations.